Kinetic form discrimination in Prader-Willi syndrome. - Fox R; Yang GS; Feurer ID; Butler MG; Thompson T (Journal of Intellectual Disability Research, 2001)
Discrimination of the shape of motion-produced forms generated by random elements (i.e. second-order stimuli varying in element density and temporal correlation) was tested in four groups: (1) subjects with Prader-Willi syndrome (PWS), chromosome 15q deletion subtype; (2) subjects with PWS, uniparental maternal disomy (UPD) subtype; (3) equivalent non-PWS controls; and (4) normal controls. The performance of the normal controls exceeded that of all other groups (78% correct, P < 0.009). The PWS deletion (66%) and the equivalent control groups (59%) did not differ (P < 0.95). The UPD group performed significantly less well (38%, P < 0.04) than all the other groups. The performance of the PWS deletion and equivalent control groups is consistent with other data indicating that these populations encounter difficulty meeting the processing demands posed by second-order stimuli. The inferior performance of the UPD group may be attributed to receiving two active alleles of a maternally expressed gene influencing neural development. One candidate is the ubiquitin protein ligase gene (UBE3A), which is maternally expressed only and localized to the 15q region. Other possibilities include the requirement of a paternally expressed gene, residual mosaic trisomy 15 in the brain tissue or complex interactions including specific ratios of differentially spliced gene products.